Comparison of MMP-9 Density Between Triple Negative and HER2 Enriched Breast Carcinoma Subtypes - Putra Pratama, Eka; Dewi, Citra; Aspitriani, Aspitriani; Bahar, Erial (Majalah Patologi Indonesia, 2023)
Background Matrix metalloproteinase-9 (MMP-9) is a protease that plays an important role in various biological processes of breast cancer. This marker may be useful in determining the prognosis and become a promising therapy, especially in breast carcinoma with an aggressive subtype including HER2 enriched and triple negative. Both subtypes have high MMP-9 expression, but it is necessary to differentiate them because they have different biological and molecular aspects. This study aims to compare the density of MMP-9 between triple negative and HER2 enriched breast carcinoma subtypes and their relationship with clinicopathological characteristics. Methods This is a cross sectional study using 32 samples of paraffin blocks and slides of breast carcinoma patients with triple negative and HER2 Enriched subtypes at the Department of Anatomical Pathology Faculty of Medicine Sriwijaya University/Dr. Mohammad Hoesin Hospital Palembang for the period January 1, 2016 to December 31, 2019. Each sample was stained with MMP-9 antibodies immunohistochemistry (polyclonal, Abcam). Comparative analysis of MMP-9 density between the two subtypes was carried out using the median value based on the Mann-Whitney analysis. MMP-9 density was categorized as high and low based on the ROC curve and analyzed by using chi-square test to assess its association with clinicopathological characteristics. Results Mann-Whitney test showed that the MMP-9 density was higher in the HER2 enriched subtype (median 12.0) than triple negative (median 8.8) with a p value of 0.632. The relationship distribution of high MMP-9 density was found in the category of age group >40 years old (60.0%), positive lymphovascular invasion (86.7%) and histological grade III (80.0%) with p values of 0.798, 0.402 and 0.691. Conclusion MMP-9 density in HER2 enriched subtype was higher than triple negative subtype, but statistically not significant.